Fractures of Gunung Ledang Granite: Insight to Post-Cretaceous Structural Event - Choong Chee Meng, Askury Abdul Kadir, Muhammad Noor Amin Zakaria, . (2017)
Based on the deformations in the Cretaceous rocks and also the results of the radiometric dating of the fault zones [Zaiton Harun, Late Mesozoic—Early Tertiary faults of Peninsular Malaysia, 9], it is proven that tectonics of onshore Peninsular Malaysia was still active during post-Cretaceous. These deformations may contribute to the basin formation/inversion during Tertiary period in Sundaland.